2021
DOI: 10.1016/j.trgeo.2021.100515
|View full text |Cite
|
Sign up to set email alerts
|

Impact of monotonic and cyclic suction variations on the thermal properties of a stabilized compacted silty soil

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The main reason for this may be that soil Ⅲ has a high water content, which weakens the solidifying effect of the solid-waste-based binder. Simultaneously, the humic acid of the organic matter in soil Ⅲ can also destroy the hydration structure, resulting in lower strength [ 36 , 37 ]. Despite that, the UCS of solidified soils Ⅰ, Ⅱ, and Ⅲ after 28 days can both satisfy the technical requirements for the cement–soil mixing pile (>0.8 MPa, YBJ 225-91 [ 38 ], Chinese standard) when the solidifying agent content is 17% (corresponding to 60 kg/m of the cement–soil mixing pile).…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for this may be that soil Ⅲ has a high water content, which weakens the solidifying effect of the solid-waste-based binder. Simultaneously, the humic acid of the organic matter in soil Ⅲ can also destroy the hydration structure, resulting in lower strength [ 36 , 37 ]. Despite that, the UCS of solidified soils Ⅰ, Ⅱ, and Ⅲ after 28 days can both satisfy the technical requirements for the cement–soil mixing pile (>0.8 MPa, YBJ 225-91 [ 38 ], Chinese standard) when the solidifying agent content is 17% (corresponding to 60 kg/m of the cement–soil mixing pile).…”
Section: Resultsmentioning
confidence: 99%
“…Clayey soils exhibit high sensitivity to variations in moisture content but are also subject to adverse impacts of environmental stressors, including climatic conditions, longterm static loading, and dynamic impacts. Therefore, stabilization of such soils, when used as road subgrade, requires remedial treatment to increase their strength properties and decrease permeability [1][2][3][4][5][6][7][8][9][10]. The use of quicklime (QL) for soil stabilization is a widely recognized technique [11].…”
Section: Introductionmentioning
confidence: 99%
“…Such a situation can be observed in certain cement treatment applications, such as deep mixing. In other applications, such as the stabilization of compacted soils, the soil remains unsaturated during the curing process and some studies showed that the curing process is associated with an increase in suction in the samples [21,22]. However, very few investigations were performed to analyze the setting reaction development as a function of the curing time under unsaturated conditions, which are more realistic for in situ soil treatment (road subbase, embankments, etc.).…”
Section: Introductionmentioning
confidence: 99%